Economic study of a pig production establishment (Costos y Gestión, 2023)
Pork production has become relevant in recent years thanks to changes in consumption habits, with the consumption of this type of meat increasing. This reality, which presents itself as an opportunity for small and medium-sized companies in the sector, finds them in many cases in situations in which they do not have an adequate use of cost techniques that allow them to generate useful and timely information for the decision-making process. In addition to this we have to consider that the pig producer is a price taker, in consequence, cost management and control becomes vital to maintain the company’s competitiveness.This paper analyzes an establishment located in the district of Bahía Blanca, in order to provide a methodology that allows timely, reliable and complete information on costs and income on the management of the agricultural company. In order to obtain information for decision making, we work by differentiating the different stages of the production process with their respective productive results.
Keywords: General Theory of Cost; pig production; transfer pricing; cost management; decision making